2020
DOI: 10.1186/s12889-020-8246-3
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the social-benefit motive among high-risk patients: a field experiment on influenza vaccination behaviour

Abstract: Background Influenza vaccine uptake remains low worldwide, inflicting substantial costs to public health. Messages promoting social welfare have been shown to increase vaccination intentions, and it has been recommended that health professionals communicate the socially beneficial aspects of vaccination. We provide the first test whether this prosocial vaccination hypothesis applies to actual vaccination behaviour of high-risk patients. Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 45 publications
(69 reference statements)
3
27
0
Order By: Relevance
“…[24][25][26] There is also recent evidence suggesting that communicating the social-benefit motives of vaccinations to hospitalized high-risk patients does not enhance actual vaccination behavior. 27 Our null results related to the effects of communicating the social benefits of vaccination parallel the emerging conclusion from the literature that information materials tailored using behavioral science techniques do not affect real vaccination rates. In contrast, there is some evidence from the low-and high-income countries that modest in-kind incentives and direct monetary incentives may increase vaccine uptake.…”
Section: Discussionsupporting
confidence: 74%
“…[24][25][26] There is also recent evidence suggesting that communicating the social-benefit motives of vaccinations to hospitalized high-risk patients does not enhance actual vaccination behavior. 27 Our null results related to the effects of communicating the social benefits of vaccination parallel the emerging conclusion from the literature that information materials tailored using behavioral science techniques do not affect real vaccination rates. In contrast, there is some evidence from the low-and high-income countries that modest in-kind incentives and direct monetary incentives may increase vaccine uptake.…”
Section: Discussionsupporting
confidence: 74%
“…We presume that public health as an issue (vs. many other issues) trends toward the higher end of the moral continuum on average, but careful testing of a communicator's target audience will be useful to identify their tendency to think of public health as a moral issue, which could help communicators tailor their message accordingly. In addition, there may be other factors that would make a self-focused message more persuasive, such as whether a person is at very high risk (e.g., Isler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…3Another stream of applied research has investigated self-interested versus prosocial motives in the context of health behavior (and especially vaccination decisions), and has provided clear evidence that both motives can encourage disease prevention [25][26][27][28][29] . A few studies have directly compared the relative effectiveness of personal versus public framing in vaccination appeals, with inconsistent results: some studies found that public framing was ineffective [30][31][32] , while others provided some mixed evidence for the effectiveness of public framing 33,34 ; and a set of field studies investigating handwashing among healthcare professionals found that it was more effective to emphasize patient safety than personal safety 35 . Thus, the literature surrounding disease spread prevention likewise does not make a clear prediction regarding the relative importance of self-interested versus prosocial motivations, and the relative efficacy of self-interested versus prosocial framing, for coronavirus prevention.To investigate, we measure the influence of three messaging treatments on intentions to engage in COVID-19 prevention behaviors: one that emphasizes personal benefits of prevention, one that emphasizes public benefits of prevention, and one that emphasizes both types of benefits.…”
mentioning
confidence: 99%